Corporations and the Uses of Law: International Investment Arbitration as a “Multilateral Legal Order" - Peter Muchlinski (Oñati Socio-Legal Series)
This paper seeks to examine the claim, made by certain legal scholars, that international investment law, though based mainly on Bilateral Investment Treaties (BITs) is in fact a multilateral order that introduces principles of an emergent “global administrative law” into the regulation of state conduct in relation to foreign investors and their investments. Such scholars argue that this order develops through the decisions of investor-State arbitral tribunals which are creating a harmonised understanding of the meaning of BIT provisions and an institutional system of adjudication that furthers the development of global administrative principles. Through a critical examination of this approach the paper argues that this field is not a multilateral order but an unstructured process of privatised legal entrepreneurship which seeks to further a professional interest in developing an extensive, investor friendly, regime of BITs. Furthermore, that process fails as a means of providing effective or legitimate legal review of administrative action.  The argument is made both on a theoretical level and by a review of a specific issue in international investment law, namely, the development of  wider types of claims and the rise of so-called “treaty shopping” by means of corporate group structuring.  In particular the multi-jurisdictional location of various affiliates in a multinational enterprise creates a network of potential claimants in investor state disputes, giving rise to the risk of multiple claims, while the possibility of setting up affiliates in various jurisdictions creates opportunities for “treaty shopping”. “Treaty shopping” involves the enterprise locating an affiliate in a jurisdiction that has signed an investment protection treaty with the host country, allowing various affiliates and/or the parent in a group enterprise to benefit from treaty protection even though they possess the nationality of a state that has no such agreement with the host. In addition “treaty shopping” can be practiced by claimants possessing the nationality of the host country itself by way of the incorporation of a “shell company” in a country that has an investment protection agreement with the host country. It is argued that interpretations of treaty provisions in this area lack real legitimacy and create unacceptable procedural burdens on the host country.